Concepções e práticas de professores em relação ás dificuldades de aprendizagem em matemática dos alunos dos 4os anos do ensino fundamental - Costa, Janíbia Fernanda da (2013)
This paper deals with a research aimed to understand the concepts and practices of teachers to remedy learning difficulties in mathematics of students in the elementary school year 4 on the schools in Cuiaba – state of Mato Grosso. This research was designed with the following problem: What are the concepts and practices of teachers on learning difficulties in mathematics of students in elementary school 4th year? Considering the nature of this research, the research methodology adopted was a qualitative approach, in which we base and Bogdan and Biklen (1994); Baraldi (1999); Lorenzato and Fiorentini (2006); Ludke & Andrew (1986); Triviños (1987). The research was conducted in two stages: at first we did a survey of Brazilian studies that discuss the Learning Difficulties in Mathematics, Mathematical Concepts in order to know what the authors say about this subject addressing teachers' conceptions. Thus, the theoretical basis regarding the Learning Difficulties in Mathematics is backed by Schmeck (1995), Kira (1983), Paín (1983); Vitti (1999), Boyer (1996); Sadovsky (2007), Brasil (1997); Engelhardt, Bermejo & Genovard (1996), among others. In relation to mathematics education, we have considered theoretically the authors Bridge (1992); Mictotti (1999); Bkouch, Charlot and Rouche (1991), Guimarães (1988), Thompson (1992); Fiorentini (1995, 2008); Libâneo (1985); Saxe (1991); Darsie (1999); Paula (2010); Kamii (1986, 1988), Becker (1992), among others. Through the theoretical and quoted the data collected, established as categories of analysis, the prospect Contemporary and Traditional Education. The second stage of our investigation was established by field research, also known as empirical, with six teachers who teach Mathematics in classes in the 4th year of primary education,in three state schools of the in Cuiaba - MT, named for Orange School , Manga School and Pitanga School. As instruments of data collection, we used questionnaires, interviews and observations on lessons. Our intention was not guided in framing the subject in one or another category, because we believe that these concepts do not emerge or reveal themselves in the subject so pure, but rather interpret their statements from the questionnaires and gifts with these approaches linked to teaching-learning process. As a result, the analyzis the data, the concepts expressed in the statements of teachers indicates that they all walk their way, to a greater or lesser degree, from both perspectives, with larger indication one of them. Thus, it is possible to say that for two subjects there is a tendency to the Contemporary Perspective, while for the other four subjects there is a tendency to Traditional Perspective. Already on teachers' practices, we found a strong tendency to Traditional conceptions, except for two teachers. This leads us to infer that the concepts and practices of teachers are mostly in disagreement.